Behaviour and design of prefabricated connections under combined bending and compression for free-form grid structures. (July 2022) - Quan, Guan; Ye, Jun; Xu, Nengbin; Qi, Jiafeng; Zhang, Zhao; Wu, Hui; Gao, Boqing
Abstract: Free-form single-layer grid shells are not uncommon in long-span stadium roofs, airport terminals, exhibition pavilions, and shopping malls, the shapes of the grid surface are usually versatile to meet the architectural requirements. This emphasizes the importance of flexible joints that can adapt to various curvatures of the free-form structures. A design procedure and formulas are therefore proposed to underpin the application of a recently proposed prefabricated joint system. Three full-scale joints with different dimensions are tested under the combined bending and compression. Finite element models are proposed and validated against the tested results. The FE models provide good predictions against the test results in terms of the initial stiffness and ultimate capacities. Parametric studies are then carried out to verify the effectiveness of the proposed design formulas, as well as to investigate the influence of the key parameters on the load-carrying capacities of the proposed joints. A wider range of FE models, with a variety of combinations of bending and compression, are developed to validate the feasibility of the design formulas. The results demonstrate that the proposed design formulas can provide a reasonably good prediction of the joint strengths and deflection. The joint system can be easily designed, prefabricated off-site and easily assembled on-site, therefore has the potential to be applied in the construction of free-form shells.